جمالية التناص في قصة ممنوع الدخوللمحمد كامل بن يزيد - هاجرة, بله باسي; إلهام, بوحامد; حنان, خشخوش; بثينة, مسغوني (جامعة الوادي - University of Eloued, 2019)
يصف الكاتب أحوال وأهوال المدينة من مرايا معكوسة وواقع أليم يراه نفسه فيه ضائعا في أفكاره وتحركاته فقال فيها المدينة ضوضاء ثم سكون ثم ضوضاء وبين كل هذا حدث كل شئ بسرعة ,فأصبحت أحشاء المدينة تتقيأ حدث مرفوضا خلف المدينة, ولم يجد إلا خفيه الحنين الذي يرافقه في المدينة الغريبة,وهنا ظهرت إمرأة مجهولة الهوية كل شيء لها مباح اليوم عكس الأمس الذي قتلت فيه, ويأتيه صيف الأوانة الأخيرة هذا الصيف الموعود هذا صيف مشهود ومن هول ما حدث في المدينة واقف على لافتة صخرية إقتربت منها بقلبا حزينا وقرأ الكتابة المنقوشة عليها "ممنوع الدخول. " Summary of the story {Forbidden Entry} By" Mohammed ElKamel Ben Zaid": The writer describes his conditions and the conditions of the city mirrors mirrored and a painful reality he sees himself lost in his thoughts and movements, where he said the city noise and then silence and then noise and among all this happened quickly, became the bowels of the city vomited an event rejected behind the city, and found only The hidden nostalgia that accompanies him in the strange city, and here appeared an unknown woman everything is possible today, unlike yesterday, in which she was killed, and comes the summer of late ,this summer promised, this summer is remarkable and the hall of what happened in the city stood on a rocky sign; Including a sad heart and read the book inscribed on them forbidden entry.
دراسات ادبية